Develops an Alarm System in the Alarm Bath and an Adaptive Power Adjustment System - Sanjar Ruzimatov; Dadaxon Fayzullayev (International Journal on Orange Technologies, 2021)
Mathematical models of the weighting process are obtained in the form of material balance equations. These mathematical models allow the identification of key factors influencing the process. A systematic algorithm for the synthesis of adaptive observers and a structure for the adaptive control system have been developed for the slowing process. The proposed algorithm allows to identify the parameters of control objects and improve the performance of adaptive monitoring devices.